LA CASTRACIÓN QUÍMICA Y SU PERTINENCIA EN LA INCORPORACIÓN A LA LEGISLACIÓN PENAL ECUATORIANA - Roblez Macas, Laura Estefanía (2019)
This thesis entitled: " The chemical castration and its relevance in the incorporation to the Ecuadorian penal legislation", it makes reference to the implementation of the chemical castration as sanctioning and rehabilitating measure of the condemned for rape crimes to minors of 14 years; At the same time, some objectives were determined, about the meticulous study, so conceptual, doctrinal and juridical of the factors involved in chemical castration, further its feasibility in Ecuador and its imposition as a sanctioning and resocializing purpose of the aggressor. Nowadays in the ecuadorian criminal law the Liberty deprivation is the unique penalty for rape crimes, punishment that doesn´t fase sexual crimes problems, neither guarantee in the victim the non-repetition right and compromises the citizenship safety. Rape crimes are despicable cause the irreparables consequences that they produce to the aggrieved, moreover, when those affected are children, defenseless beings who don´t have all the capacities to defend themselves, which makes the illicit abominable and causes general aversion. Imagine the possibility that many of these crimes can be avoided through the application of chemical castration, it opens the doors to analyze in depth its positives and negatives consequences, likewise, consider the obvious features of both the aggressor and the victim, and thus, determine its relevance in Ecuador. In the same way, through the use of materials and methods, the execution of surveys and interviews, the verification of objectives and the testing of the hypothesis; they have allowed to verify the stipulated problematic and in this way to propose a legal project of reform to the Integral Penal Organic Code, to guarantee the rights of those affected as to provide citizen security.